2016
DOI: 10.1016/j.jbusres.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Identifying moderators of brand attachment for driving customer purchase intention of original vs counterfeits of luxury brands

Abstract: Few studies have examined the relationships between brands and consumers in the context of counterfeiting. In this context, this research aims to explore how the attachment of a consumer with a luxury brand can affect her/his decision to buy counterfeits, and how this relates to her/his public self-consciousness. Two survey based studies were conducted among potential counterfeit buyers in Brazil. A sample of middle-class female fashion shoppers from Brazil was used to test the hypotheses in study 1 (n = 532) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(167 citation statements)
references
References 88 publications
(149 reference statements)
9
151
1
6
Order By: Relevance
“…In accordance with Yoo and Lee (), Lianto (), and Kaufmann et al (), our results confirm the positive effects of perceived economic benefits and perceived hedonic benefits on intentions of purchasing counterfeits. The studies of Yoo and Lee (), Lianto (), and Kaufmann et al () were conducted in South Korea, Indonesia, and Brazil, respectively. This study extends the results to Tunisia.…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with Yoo and Lee (), Lianto (), and Kaufmann et al (), our results confirm the positive effects of perceived economic benefits and perceived hedonic benefits on intentions of purchasing counterfeits. The studies of Yoo and Lee (), Lianto (), and Kaufmann et al () were conducted in South Korea, Indonesia, and Brazil, respectively. This study extends the results to Tunisia.…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 99%
“…The effect of attitude toward counterfeits by considering hedonic benefits on purchase intention of counterfeit products confirms the findings of Yoo and Lee (), Kaufmann et al (), and Lianto (). Future research could extend this conceptual model by considering the emotional reactions that are related to the purchase of counterfeit products.…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaufmann, Petrovici, Filho, and Ayres () explained their model based on TRA and attachment theory, therefore they suggested that the stronger the purchasing intentions in buying counterfeits, the lower the purchasing intentions to buy original luxury fashion brands. There is a positive impact of economic benefits on the purchasing intention of counterfeits whereas brand attachment has negative.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of this communication depends on the well understanding of consumer needs and behavior by identifying their needs and provides them with the correct service at the accurate time in the precise place [38]. It is very important to make sure that the appropriate media is used [39]. Multiple channels of communication networks in Arab regions pose a big challenge to Arabic Marketers to reach their target consumers especially that traditional marketing media is losing its importance by challenging with the novel social media.…”
Section: Table 1 -Definitions Of Scientist About Social Media In Commmentioning
confidence: 99%